Doctors’self-prescribing behavior: an exploratory study - Mir, Shakeel Ahmad; Ahangar, Junaid Ahmed; Shakeel, Danish (International Journal of Research in Medical Sciences, 2020)
Background: Self-prescribing among doctors is common. But the General Medical Council (GMC) and American Medical Council recommend that doctors should avoid prescribing for themselves, and close family members. Self-prescribing can lead to serious consequences. The present study reports the prevalence and pattern of self-prescribing among doctors working in various healthcare facilities of Kashmir Valley. Methods: Pre-validated questionnaires were sent to 200 doctors selected by convenience sampling. Only 184 returned the completely filled questionnaires. Results: At which 95.7% male doctors and 97.8% female doctors were self-prescribing. 100% doctors above the age of 40 years were self-prescribing. 100% post graduate students and consultants were practicing self-prescribing. 98.0% of those active as doctors for 1-5 years and 95.1% of those active for more than five years were self-prescribing. 60.7% doctors cited convenience, 40.4% time saving, 27.0% quick relief, 60.7% confidence, 14.6% low cost of treatment, and 15.7% crowd avoidance as a reason for self-prescribing. Major diseases self-treated were: headache (78.7%), respiratory symptoms (79.8%), fever (53.9%) and pain syndromes (31.5%). Major drugs used were: analgesics (80.9%), antipyretics (68.5%), antibiotics (58.4%), decongestants (49.4%) and antispasmodics (33.7%). Conclusions: The observed prevalence of self-prescribing was very high in this study. The issue of self-prescribing is common and requires attention.